Cognitive–behaviour therapy for post-traumatic stress in schizophrenia. A randomized controlled trial. Issue 1 (21st September 2016) - Steel, C.; Hardy, A.; Smith, B.; Wykes, T.; Rose, S.; Enright, S.; Hardcastle, M.; Landau, S.; Baksh, M. F.; Gottlieb, J. D.; Rose, D.; Mueser, K. T.
Abstract : Background: There is limited evidence for effective interventions in the treatment of post-traumatic stress symptoms within individuals diagnosed with schizophrenia. Clinicians have concerns about using exposure treatments with this patient group. The current trial was designed to evaluate a 16-session cognitive restructuring programme, without direct exposure, for the treatment of post-traumatic stress symptoms specifically within individuals diagnosed with schizophrenia. Method: A multicentre randomized controlled single-blinded trial with assessments at 0 months, 6 months (post-treatment) and 12 months (follow-up) was conducted. A total of 61 participants diagnosed with schizophrenia and exhibiting post-traumatic stress symptoms were recruited. Those randomized to treatment were offered up to 16 sessions of cognitive–behaviour therapy (CBT, including psychoeducation, breathing training and cognitive restructuring) over a 6-month period, with the control group offered routine clinical services. The main outcome was blind rating of post-traumatic stress symptoms using the Clinician Administered PTSD Scale for Schizophrenia. Secondary outcomes were psychotic symptoms as measured by the Positive and Negative Symptom Scale and the Psychotic Symptom Rating Scale. Results: Both the treatment and control groups experienced a significant decrease in post-traumatic stress symptoms over time but there was no effect of the addition of CBT on either the primary or secondary outcomes. Conclusions: The current trial did not demonstrate any effect in favour of CBT. Cognitive restructuring programmes may require further adaptation to promote emotional processing of traumatic memories within people diagnosed with a psychotic disorder.